2010
DOI: 10.1111/j.1747-5457.2011.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Neotectonic Controls on Petroleum Accumulations, Offshore China

Abstract: Tectonic activity offshore China during the Late Miocene and Quaternary (“neotectonism”) generated unconformities, resulted in depocentre migration, created new faults and initiated earthquake activity. This episode of structural disturbance, which occurred during post‐rift thermal subsidence, modified pre‐existing hydrocarbon accumulations and formed new pools. Constructive effects of neotectonism occurred in the Bozhong Depression, Zhu #2 Depression and the Yinggehai Basin. These effects included the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Understanding basin-scale subsurface fluid flow is critical to petroleum exploration (e.g., Bethke et al, 1991;Gong et al, 2011), geological CO 2 sequestration (e.g., Birkholzer et al, 2009;Person et al, 2010), and contaminant transport modeling (e.g., Carle et al, 2006). In rift basins, factors affecting regional flow patterns include variations in sediment type (Person and Garven, 1994;Mailloux et al, 1999), basin subsidence and/ or compaction (Cathles and Smith, 1983;Cartwright, 1994), and hydrothermal circulation (Person and Garven, 1992;Simms and Garven, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding basin-scale subsurface fluid flow is critical to petroleum exploration (e.g., Bethke et al, 1991;Gong et al, 2011), geological CO 2 sequestration (e.g., Birkholzer et al, 2009;Person et al, 2010), and contaminant transport modeling (e.g., Carle et al, 2006). In rift basins, factors affecting regional flow patterns include variations in sediment type (Person and Garven, 1994;Mailloux et al, 1999), basin subsidence and/ or compaction (Cathles and Smith, 1983;Cartwright, 1994), and hydrothermal circulation (Person and Garven, 1992;Simms and Garven, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This was especially the case during the Pliocene, when the depression experienced another episode of structural disturbance along the Tanlu Fault (Gong, 2004). The fault is a transtensional fault extending over 400 km offshore from Liaodong Bay in the north to the Liaozhou Bay in the south.…”
Section: Tectonic Settingsmentioning
confidence: 97%
“…These explorationists, based on the common association of source rock presence with high rates of subsidence in the onshore depressions, speculated that rapid Neogene subsidence could have generated a new suite of source potential previously ignored and that recent fault movements along the Tanlu Fault could have provided needed conduits for upward hydrocarbon migration into Neogene reservoirs (Zhu and Wang, 2000;Gong and Wang, 2001;Gong, 2004). Sequence stratigraphic studies showed fluvial systems drained toward the depression center, where the predicted lacustrine environments could provide the needed regional top seals (Mi, 2001).…”
Section: Development Of Exploration Conceptsmentioning
confidence: 98%
See 2 more Smart Citations